What Distinguishes Singing as a Unique Form of Expression? - Peter Ong (PT FORMOSA CENDEKIA GLOBAL, 2023)
Singing has consistently been regarded as a fundamental aspect of human expression, transcending cultural boundaries and serving as a universally practised pastime. The act of singing is widely recognised for its ability to elicit feelings of happiness and provide a means of emotional expression. However, an increasing body of research suggests that singing also yields other beneficial outcomes in the realms of social interaction, psychological well-being, and physical health. This qualitative study aims to explore the advantages of regular singing through in-depth interviews with a sample of 10 individuals. The activity of vocalising musical sounds, commonly referred to as singing, has been observed to have a positive impact on an individual's psychological state, specifically their mental well-being. This is attributed to the cultivation of a sense of purpose and accomplishment that singing facilitates. The act of performing in front of an audience or effectively mastering a challenging musical piece have the capacity to positively impact an individual's mental well-being. The findings additionally suggested that engaging in singing has the capacity to substantially enhance an individual's overall state of health and level of satisfaction with life, regardless of whether it is performed privately in a personal setting, as a member of a choral ensemble, or as a vocation within the realm of music.